Predicting refractoriness in lateral epicondylitis using initial grip strength and quickdash: a retrospective cohort study - Kazuhiro Ikeda; Akira Ikumi; Shinzo Onishi; Takeshi Ogawa; Sho Kohyama; Yuichi Yoshii (BMC Musculoskeletal Disorders)
Abstract Background Lateral epicondylitis is a self-limited disease and refractory condition; thus providing optimal treatment is challenging. This study investigated a method for predicting cases that would not improve sufficiently under a wait-and-see policy using clinical indicators obtained during the initial consultation. Methods Twenty-two patients with lateral epicondylitis prescribed a resting orthosis and followed up for 6 months were included. Grip strength ratios for affected/unaffected side; quick disabilities of the arm, shoulder, and hand (QuickDASH) scores were measured at 6-week intervals. Receiver operating characteristic curves for predicting refractory cases were created from the initial measurement items to determine the cut-off values and prediction accuracy. Results The 6-month post-treatment QuickDASH scores for the 14 improved patients and 8 refractory patients were 2.3 ± 4.7 and 25.9 ± 15.4, respectively. Grip strength ratios significantly predicted refractoriness risk with a 0.54 cut-off value. The QuickDASH scores significantly predicted refractoriness risk with a 30-point cut-off value. Meeting either of these cutoff values achieved a sensitivity of 1.0 for predicting refractoriness. Conclusions The patients with a grip strength ratio ≤ 0.5 on the affected side or a QuickDASH score ≥ 30 at initial consultation continued having symptoms 6 months after conservative treatment.